1983
DOI: 10.1084/jem.158.4.1338
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and serum amyloid P component stimulate C3b- and C3bi-mediated phagocytosis in cultured human monocytes.

Abstract: Receptors for C3 exist in two states, an active state in which the receptors promote phagocytosis and an inactive state in which they do not . For example, cultured human monocytes (MO) bear separate receptors that bind C3b-and C3bi-coated erythrocytes, but neither receptor promotes phagocytosis of such C3-coated erythrocytes (1) . Brief stimulation ofthe MO with the tumor promoter phorbol myristate acetate (PMA), however, renders both C3 receptors competent to generate a phagocytec response . Similarly, C3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(104 citation statements)
references
References 17 publications
2
102
0
Order By: Relevance
“…Adhesion of macrophages to matrix components may modulate complement receptor function [37,38] and phagocytosis via ␣ 5 ␤ 1 [39]. It is interesting to note that Blystone and colleagues found that binding of fibronectin-coated particles to Fig.…”
Section: Role Of Fibronectin Domains In Augmentation Of Phagocytosismentioning
confidence: 99%
“…Adhesion of macrophages to matrix components may modulate complement receptor function [37,38] and phagocytosis via ␣ 5 ␤ 1 [39]. It is interesting to note that Blystone and colleagues found that binding of fibronectin-coated particles to Fig.…”
Section: Role Of Fibronectin Domains In Augmentation Of Phagocytosismentioning
confidence: 99%
“…Because PMN can ingest unopsonized zymosan through CD11b/ CD18, it was possible that SAP and CRP were providing an activating signal for uptake of zymosan through these receptors (33) rather than directly binding to Fc␥R to promote ingestion of zymosan. Therefore, we also tested the ability of SAP and CRP to opsonize Dynabeads, which are not bound or ingested by PMN in the absence of opsonins (phagocytic and attachment indexes Ͻ10).…”
Section: Phagocytosis Of Beadsmentioning
confidence: 99%
“…The biologic function of the receptor probably varies according to the cell type on which it resides. It is involved in endocytic reactions of neutrophils and monocytes (25)(26)(27)(28)(29)(30)(31)(32)(33), and it endows erythrocytes with a potential capacity for adsorbing immune complexes in the circulation (34). Its function on lymphocytes remains largely unknown, although it may enhance response of B cells to other stimulatory factors (35).…”
Section: The Structure and Function Of The 3 Types Of C3 Receptorsmentioning
confidence: 99%